A novel tacholess order tracking method for gearbox vibration signal based on extremums search of gearmesh harmonic. (15th April 2023) - Xu, Lei; Ding, Kang; He, Guolin; Li, Weihua; Li, Jie
Highlights: Order tracking was realized based on extremums search of gearmesh harmonic. Shaft phase vs time map was constructed without integral error. The process error is analyzed mathematically. A designed scheme is provided to eliminate the process error. The effectiveness and robustness were verified in simulation and experiment. Abstract: Computed order tracking (COT) is an effective vibration analysis method for mechanical equipment operating at time-varying speed. The principle is to resample the time-domain sampled vibration data under the guidance of angle information of reference shaft. The rotation angle obtained from numerical integration is generally limited by the deviation of integration on rotation speed. To address this problem, a novel acquisition method of rotation angle is proposed to improve the precision of order tracking analysis. Based on the equi-angular relationship between adjacent peaks of a single gearmesh harmonic, the discrete shaft phase vs time map is directly established by obtaining the peak time. The process error is thoroughly investigated, and a designed scheme is provided to eliminate the effects of discrete sampling and amplitude modulation. Theoretically, the rotation angle can be correctly depicted, which is useful for a highly precise order-tracking analysis. The accurate amplitude and high condensed spectral lines of order spectrum are achieved both in the simulation and experiment signals, which verified the effectiveness and robustness of the proposed method. It is helpful for the accurate reconstruction of speed-related vibration signal in the order spectrum, and enhances the capability of condition monitoring on gear systems.